Políticas coloniales y agendas locales en los márgenes del imperio español : La deportación de vagos mexicanos a las Filipinas, 1765-1811 - Eva Maria Mehl (Les Cahiers de Framespa)
This study focuses on the implementation of late Bourbon policies against vagrancy in Spain and the viceroyalty of New Spain. Using the royal decree that in 1775 instituted annual roundups of vagrants in Spain as a point of departure, the first half of this article analyzes the reasons why this ordinance was adopted in Mexico City in 1783 with the purpose of sending vagrants to the Philippines in a systematic manner and complementing the annual quota of soldiers that New Spain had to send to the archipelago. The second part of this study examines the consequences of this decision in New Spain’s society and for the imperial needs of the Spanish Philippines.